Goldilocks and the three TILs - Dada, H; Dustin, ML (Rockefeller University Press, 2022)
In this issue of JEM, Shakiba et al. (2021. J. Exp. Med. https://doi.org/10.1084/jem.20201966) tell a tale of three tumor infiltrating lymphocytes (TILs). The first TIL was too strong and became exhausted. The second TIL was too weak and became inert. The third TIL lost CD8, and this made it just right.